A comparison of field and laboratory testing of sports specific fitness for female field hockey players - Kusnanik, N. W. (2001)
There are many methods to measure the physical fitness of athletes, including tests that can be applied in the field or in the laboratory. Much of the recent research with regard to fitness of team sport players has been undertaken using laboratory testing to measure aerobic power, anaerobic power and capacity, strength and flexibility. Field tests are an alternative method to measure the fitness of players without the expense, time and expertise required for the laboratory testing, especially in developing countries. The purpose of this study is to establish procedures for the application of contemporary sports science practice for Indonesian female field hockey players, including determination of the precision of field tests of the physical and performance characteristics of field hockey players in Indonesia; determination of the physical and performance characteristics of Indonesian female field hockey players; identification of the performance demands and distance covered during competitive field hockey at the national level in Indonesia; comparison of the physical and performance characteristics of national level female field hockey players in Indonesia with those of club level players in Australia; and determination of the relationships between field and laboratory tests of physiological performance capacity for field hockey. Due to conversion problems, five paragraphs have been omitted. For full abstract, see 01front.pdf. In conclusion, the present study found that the Indonesian female field hockey players (at the national level) were comparable to the Australian female field hockey players (at the club level) in some physical and performance test results. However, they were also different on other physical and performance characteristic measurements, with the Indonesian players generally have lower values, for other performance measurements.